Examination of the influence of cedar fragrance on cognitive function and behavioral and psychological symptoms of dementia in Alzheimer type dementia - Yuya Takahashi; Sho Shindo; Takashi Kanbayashi; Masahiro Takeshima; Aya Imanishi; Kazuo Mishima (Wiley, 2020)
Abstract We examined whether symptoms of dementia are improved by olfactory nerve stimulation in Alzheimer type dementia patients. First, a stick‐type olfactory identification ability test was performed in patients with Alzheimer type dementia, to select patients without olfactory dysfunctions. Then, these patients were randomly assigned into the intervention (n = 19) and the control groups (n = 17). To evaluate the effects of olfactory nerve stimulation, we exposed the intervention group to a disinfecting ethanol with added aroma extracts from ceder and the control group to the ethanol without the added aroma extracts. Each group underwent the intervention for 8 weeks, cognitive and behavioral functions were evaluated before and after treatments using the Neuropsychiatric Inventory (NPI), the Japanese version of Zarit Caregiver Burden interview (J‐ZBI), and the Alzheimer's Disease Assessment Scale‐cognitive subscale (ADAS‐cog). A significant improvement was observed in the NPI score and J‐ZBI in the intervention group compared to the control group at 4 and 8 weeks. On the other hand, there was no significant difference in the score of ADAS‐cog. Exposure to cedar fragrance improved behavioral and psychological symptoms of dementia (BPSD) in Alzheimer type dementia and may reduce the burden of nursing care. In addition to its effectiveness, the procedure is simple and minimally invasive and would be a valuable non‐pharmaceutical treatment.